Movement and Song Idiom Traditional to Enhance Early Mathematical Skills: Gelantram Audio-visual Learning Media - Hidayatulloh, Taufik; Yetti, Elindra; Hapidin (Jurnal Pendidikan Usia Dini, 2020)
Many studies have shown a link between being competent in early mathematics and achievement in school. Early math skills have the potential to be the best predictors of later performance in reading and mathematics. Movement and songs are activities that children like, making it easier for teachers to apply mathematical concepts through this method. This study aims to develop audio-visual learning media in the form of songs with a mixture of western and traditional musical idioms, accompanied by movements that represent some of the teaching of early mathematics concepts. The stages of developing the ADDIE model are the basis for launching new learning media products related to math and art, and also planting the nation's cultural arts from an early age. These instructional media products were analyzed by experts and tested for their effectiveness through experiments on five children aged 3-4 years. The qualitative data were analyzed using transcripts of field notes and observations and interpreted in a descriptive narrative. The quantitative data were analyzed using gain score statistics. The results showed that there was a significant increase in value for early mathematical understanding of the concepts of geometry, numbers and measurement through this learning medium. The results of the effectiveness test become the final basis of reference for revision and complement the shortcomings of this learning medium. Further research can be carried out to develop other mathematical concepts through motion and song learning media, and to create experiments with a wider sample. Keywords: Early Mathematical Skills, Movement and Song Idiom Traditional, Audio-visual Learning Media References An, S. A., & Tillman, D. A. (2015). Music activities as a meaningful context for teaching elementary students mathematics: a quasi-experiment time series design with random assigned control group. European Journal of Science and Mathematics Education, 3(1), 45–60. https://doi.org/10.1038/srep15999 An, S., Capraro, M. M., & Tillman, D. A. (2013). Elementary Teachers Integrate Music Activities into Regular Mathematics Lessons: Effects on Students’ Mathematical Abilities. Journal for Learning through the Arts: A Research Journal on Arts Integration in Schools and Communities, 9(1). https://doi.org/10.21977/d99112867 Austin, A. M. B., Blevins-Knabe, B., Ota, C., Rowe, T., & Lindauer, S. L. K. (2011). Mediators of preschoolers’ early mathematics concepts. Early Child Development and Care, 181(9), 1181–1198. https://doi.org/10.1080/03004430.2010.520711 Barrett, J. E., Cullen, C., Sarama, J., Miller, A. L., & Rumsey, C. (2011). Children ’ s unit concepts in measurement : a teaching experiment spanning grades 2 through 5. 637–650. https://doi.org/10.1007/s11858-011-0368-8 Basco, R. O. (2020). Effectiveness of Song, Drill and Game Strategy in Improving Mathematical Performance. International Educational Research, 3(2), p1. https://doi.org/10.30560/ier.v3n2p1 Bausela Herreras, E. (2017). Risk low math performance PISA 2012: Impact of assistance to Early Childhood Education and other possible cognitive variables. Acta de Investigación Psicológica, 7(1), 2606–2617. https://doi.org/10.1016/j.aipprr.2017.02.001 Buchoff, R. (2015). Childhood Education. January. https://doi.org/10.1080/00094056.1995.10521830 Clements, D. H. (2014). Geometric and Spatial Thinking in Young Children. In Science of Advanced Materials (Vol. 6, Issue 4). National Science Foundation. https://doi.org/10.1166/sam.2014.1766 Clements, D. H., Baroody, A. J., Joswick, C., & Wolfe, C. B. (2019). Evaluating the Efficacy of a Learning Trajectory for Early Shape Composition. XX(X), 1–22. https://doi.org/10.3102/0002831219842788 Clements, D. H., Swaminathan, S., Anne, M., & Hannibal, Z. (2016). Young Children ’ s Concepts of Shape. 30(2), 192–212. Cross, C. T., Woods, T., & Schweingruber, H. (2009). Mathematics Learning in Early Chidhood Paths Toward Excellence and Equity. The National Academies Press. Geary, D. C. (2011). Cognitive predictors of achievement growth in mathematics: A 5-year longitudinal study. Developmental Psychology, 47(6), 1539–1552. https://doi.org/10.1037/a0025510 Geary, D. C. (2012). Learning Disabilities and Persistent Low Achievement in Mathematics. J Dev Behav Pediatr., 32(3), 250–263. https://doi.org/10.1097/DBP.0b013e318209edef.Consequences Gejard, G., & Melander, H. (2018). Mathematizing in preschool : children ’ s participation in geometrical discourse. 1807. https://doi.org/10.1080/1350293X.2018.1487143 Harususilo, Y. E. (2020). Skor PISA Terbaru Indonesia, Ini 5 PR Besar Pendidikan pada Era Nadiem Makarim. https://pusmenjar.kemdikbud.go.id/ Hsiao, T. (1999). Romanticism with Deep Affection: Selected Articles About the Music of Hsiao Tyzen (Hengzhe Lin (ed.)). Wang Chun Feng Wen Hua Fa Xing. Kasuya-Ueba, Y., Zhao, S., & Toichi, M. (2020). The Effect of Music Intervention on Attention in Children: Experimental Evidence. Frontiers in Neuroscience, 14(July), 1–15. https://doi.org/10.3389/fnins.2020.00757 Kołodziejski, M., Králová, P. D. E., & Hudáková, P. D. J. (2014). Music and Movement Activities and Their Impact on Musicality and Healthy Development of a Child. Journal of Educational Revies, 7(4). Kristanto, W. (2020). Javanese Traditional Songs for Early Childhood Character Education. 14(1), 169–184. Litkowski, E. C., Duncan, R. J., Logan, J. A. R., & Purpura, D. J. (2020). When do preschoolers learn specific mathematics skills? Mapping the development of early numeracy knowledge. Journal of Experimental Child Psychology, 195, 104846. https://doi.org/10.1016/j.jecp.2020.104846 Logvinova, O. K. (2016). Socio-pedagogical approach to multicultural education at preschool. Procedia - Social and Behavioral Sciences, 233(May), 206–210. https://doi.org/10.1016/j.sbspro.2016.10.203 Lopintsova, O., Paloniemi, K., & Wahlroos, K. (2012). Multicultural Education through Expressive Methods in Early Childhood Education. Ludwig, M. ., Marklein, M. ., & Song, M. (2016). Arts Integration: A Promising Approach to Improving Early Learning. American Institutes for Research. Macdonald, A., & Lowrie, T. (2011). Developing measurement concepts within context : Children ’ s representations of length. 27–42. https://doi.org/10.1007/s13394-011-0002-7 Mans, M. (2002). Playing The Music- Comparing Perfomance of Children’s Song and dance in Traditional and Contemporary Namibian Education. In The Arts in Children’s Live (pp. 71–86). Kluwer Academic Publishers. Maričić, S. M., & Stamatović, J. D. (2017). The Effect of Preschool Mathematics Education in Development of Geometry Concepts in Children. 8223(9), 6175–6187. https://doi.org/10.12973/eurasia.2017.01057a Missall, K., Hojnoski, R. L., Caskie, G. I. L., & Repasky, P. (2015). Home Numeracy Environments of Preschoolers: Examining Relations Among Mathematical Activities, Parent Mathematical Beliefs, and Early Mathematical Skills. Early Education and Development, 26(3), 356–376. https://doi.org/10.1080/10409289.2015.968243 Moreno, S., Bialystok, E., Barac, R., Schellenberg, E. G., Cepeda, N. J., & Chau, T. (2011). Short-term music training enhances verbal intelligence and executive function. Psychological Science, 22(11), 1425–1433. https://doi.org/10.1177/0956797611416999 Nketia, J. H. K. (1982). Developing Contemporary Idioms out of Traditional Music. Studia Musicologica Academiae Scientiarum Hungaricae, 24, 81. https://doi.org/10.2307/902027 Nyota, S., & Mapara, J. (2008). Shona Traditional Children ’ s Games and Play : Songs as Indigenous Ways of Knowing. English, 2(4), 189–203. Östergren, R., & Träff, U. (2013). Early number knowledge and cognitive ability affect early arithmetic ability. Journal of Experimental Child Psychology, 115(3), 405–421. https://doi.org/10.1016/j.jecp.2013.03.007 Pantoja, N., Schaeffer, M. W., Rozek, C. S., Beilock, S. L., & Levine, S. C. (2020). Children’s Math Anxiety Predicts Their Math Achievement Over and Above a Key Foundational Math Skill. Journal of Cognition and Development, 00(00), 1–20. https://doi.org/10.1080/15248372.2020.1832098 Papadakis, Stamatios, Kalogiannakis, M., & Zaranis, N. (2017). Improving Mathematics Teaching in Kindergarten with Realistic Mathematical Education. Early Childhood Education Journal, 45(3), 369–378. https://doi.org/10.1007/s10643-015-0768-4 Papadakis, Stamatios, Kalogiannakis, M., & Zaranis, N. (2018). The effectiveness of computer and tablet assisted intervention in early childhood students’ understanding of numbers. An empirical study conducted in Greece. Education and Information Technologies, 23(5), 1849–1871. https://doi.org/10.1007/s10639-018-9693-7 Papadakis, Stamatis, Kalogiannakis, M., & Zaranis, N. (2016). Comparing Tablets and PCs in teaching Mathematics: An attempt to improve Mathematics Competence in Early Childhood Education. Preschool and Primary Education, 4(2), 241. https://doi.org/10.12681/ppej.8779 Paul, T. (2019). Mathematics and music : loves and fights To cite this version. PISA worldwide ranking; Indonesia’s PISA results show need to use education resources more efficiently, (2016). Phyfferoen, D. (2019). The Dagbon Hiplife Zone in Northern Ghana Contemporary Idioms of Music Making in Tamale. 1(2), 81–104. Purpura, D. J., Napoli, A. R., & King, Y. (2019). Development of Mathematical Language in Preschool and Its Role in Learning Numeracy Skills. In Cognitive Foundations for Improving Mathematical Learning (1st ed., Vol. 5). Elsevier Inc. https://doi.org/10.1016/b978-0-12-815952-1.00007-4 Ribeiro, F. S., & Santos, F. H. (2020). Persistent Effects of Musical Training on Mathematical Skills of Children With Developmental Dyscalculia. Frontiers in Psychology, 10(January), 1–15. https://doi.org/10.3389/fpsyg.2019.02888 Roa, R., & IA, C. (2020). Learning Music and Math, Together as One: Towards a Collaborative Approach for Practicing Math Skills with Music. In I. T. (eds) Nolte A., Alvarez C., Hishiyama R., Chounta IA., Rodríguez-Triana M. (Ed.), Collaboration Technologies and Social Computing. Col (Vol. 26, Issue 5, pp. 659–669). https://doi.org/https://doi.org/10.1007/978-3-030-58157-2_10 Sarama, J., & Clements, D. H. (2006a). Mathematics, Young Students, and Computers: Software, Teaching Strategies and Professional Development. The Mathematics Educato, 9(2), 112–134. Sarama, J., & Clements, D. H. (2006b). Mathematics in early childhood. International Journal of Early Childhood, 38(1). https://doi.org/10.1007/bf03165980 Sarkar, J., & Biswas, U. (2015). The role of music and the brain development of children. 4(8), 107–111. Sheridan, K. M., Banzer, D., Pradzinski, A., & Wen, X. (2020). Early Math Professional Development: Meeting the Challenge Through Online Learning. Early Childhood Education Journal, 48(2), 223–231. https://doi.org/10.1007/s10643-019-00992-y Silver, A. M., Elliott, L., & Libertus, M. E. (2021). When beliefs matter most: Examining children’s math achievement in the context of parental math anxiety. Journal of Experimental Child Psychology, 201, 104992. https://doi.org/10.1016/j.jecp.2020.104992 Sterner, G., Wolff, U., & Helenius, O. (2020). Reasoning about Representations: Effects of an Early Math Intervention. Scandinavian Journal of Educational Research, 64(5), 782–800. https://doi.org/10.1080/00313831.2019.1600579 Temple, B. A., Bentley, K., Pugalee, D. K., Blundell, N., & Pereyra, C. M. (2020). Using dance & movement to enhance spatial awareness learning. Athens Journal of Education, 7(2), 153–167. https://doi.org/10.30958/aje.7-2-2 Thippana, J., Elliott, L., Gehman, S., Libertus, K., & Libertus, M. E. (2020). Parents’ use of number talk with young children: Comparing methods, family factors, activity contexts, and relations to math skills. Early Childhood Research Quarterly, 53, 249–259. https://doi.org/10.1016/j.ecresq.2020.05.002 Tsai, Y. (2017). Taiwanese Traditional Musical Idioms Meet Western Music Composition: An Analytical and Pedagogical Approach to Solo Piano Works by Tyzen Hsiao. http://aquila.usm.edu/dissertations/1398 Upadhyaya, D. (2017). Benefits of Music and Movement in young children. Furtados School of Music. https://www.linkedin.com/pulse/benefits-music-movement-young-children-dharini-upadhyaya Vennberg, H., Norqvist, M., Bergqvist, E., Österholm, M., Granberg, C., & Sumpter, L. (2018). Counting on: Long Term Effects of an Early Intervention Programme. 4, 355–362. http://urn.kb.se/resolve?urn=urn:nbn:se:umu:diva-148101 Verdine, B. N., Lucca, K. R., Golinkoff, R. M., Hirsh-, K., & Newcombe, N. S. (2015). The Shape of Things : The Origin of Young Children ’ s Knowledge of the Names and Properties of Geometric Forms. 8372(October). https://doi.org/10.1080/15248372.2015.1016610 Wakabayashi, T., Andrade-Adaniya, F., Schweinhart, L. J., Xiang, Z., Marshall, B. A., & Markley, C. A. (2020). The impact of a supplementary preschool mathematics curriculum on children’s early mathematics learning. Early Childhood Research Quarterly, 53, 329–342. https://doi.org/10.1016/j.ecresq.2020.04.002 Wardani, I. K., Djohan, & Sittiprapaporn, P. (2018). The difference of brain activities of musical listeners. 1st International ECTI Northern Section Conference on Electrical, Electronics, Computer and Telecommunications Engineering, ECTI-NCON 2018, 181–184. https://doi.org/10.1109/ECTI-NCON.2018.8378307 Winter, E., & Seeger, P. (2015). The Important Role of Music in Early Childhood Learning. Independent School. Zaranis, N., Kalogiannakis, M., & Papadakis, S. (2013). Using Mobile Devices for Teaching Realistic Mathematics in Kindergarten Education. Creative Education, 04(07), 1–10. https://doi.org/10.4236/ce.2013.47a1001